A 5-year longitudinal study of macular atrophy - Pinheiro, Rosa Lomelino (2022)
Macular atrophy (MA) is one of the late stages of age-related macular degeneration (AMD) and leads to irreversible loss of visual function. During the past years, efforts have been made towards a more detailed comprehension of the characteristics of MA, and a panel of retina specialists has recently established a new classification system to describe atrophy in the context of neovascular AMD, by the CONAN group. Furthermore, recent publications have focused on investigating the progression of MA, as well as the factors that might influence MA growth rates, particularly anti-VEGF injections.